2006
DOI: 10.1007/s11104-005-1302-z
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Climatic Variables and Sap Flow, Stem Water Potential and Maximum Daily Trunk Shrinkage in Lemon Trees

Abstract: The feasibility of obtaining sap flow (SF), maximum daily trunk shrinkage (MDS) and midday stem water potential (Y stem ) baselines or reference values for use in irrigation scheduling was studied in adult Fino lemon trees (Citrus limon (L.) Burm. fil.) grafted on sour orange (C. aurantium L.) rootstocks. Plants were irrigated daily above their water requirements in order to obtain non-limiting soil water conditions. The results indicated that baselines for plant-based water status indicators (MDS, SF and Y st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
0
8

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(40 citation statements)
references
References 28 publications
6
26
0
8
Order By: Relevance
“…Numerous studies (McCutchan and Shackel, 1992;Shackel et al, 1997;Naor, 2000;Choné et al, 2001;Ortuño et al, 2006) propose the measurement of stem water potential (Ψ st ) as an alternative to leaf water potential. It is defined as the water potential measured in a non-transpiring leaf in balance with the xylem after being wrapped in a bag for 2-3 hours.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies (McCutchan and Shackel, 1992;Shackel et al, 1997;Naor, 2000;Choné et al, 2001;Ortuño et al, 2006) propose the measurement of stem water potential (Ψ st ) as an alternative to leaf water potential. It is defined as the water potential measured in a non-transpiring leaf in balance with the xylem after being wrapped in a bag for 2-3 hours.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, Ψ st has been used, given that, according to numerous authors (Choné et al, 2001;Naor, 2006;Ortuño et al, 2006), is a significant and more reliable indicator of water status and early water deficit in plants, and it is considered an useful tool for irrigation scheduling in fruit trees. Other advantages are that it offers less variability and that it seems to be wellrelated to tree and fruit growth and quality on a wide range of soils and with different irrigation systems.…”
Section: Introductionmentioning
confidence: 99%
“…Con las relaciones obtenidas se puede acceder a conocer el valor de referencia del indicador a partir de los parámetros climáticos que más convenga, aunque deben de ser usadas dentro de sus límites de confianza. Ortuño et al (2006b), utilizando datos obtenidos de Abril a Enero, encontraron en limoneros adultos que el FS y el Ψ tallo correlacionan mejor con la evapotranspiración del cultivo de referencia (ETo), calculada usando la ecuación de Penman-Monteith (Allen et al 1998) (Figura 3), mientras que la MXC lo hace con la temperatura media diaria (Figura 4), a pesar de que la temperatura no es un indicador adecuado de la demanda evaporativa (Hatfield y Fuchs, 1990). No obstante, otros autores también han encontrado buenas relaciones entre los valores de la MXC y la temperatura del aire en almendro y olivo (Fereres y Moreno et al, 2006).…”
Section: Obtención De Niveles De Referenciaunclassified
“…Figura 4. Relación entre la temperatura media diaria y la máxima contracción diaria (MXC) de los troncos de limoneros adultos bajo condiciones no limitantes de riego (Adaptada de Ortuño et al, 2006b) No obstante, cabe señalar que ya en 1989 Li et al indicaron las ventajas de la programación del riego del melocotonero en función de un valor de la máxima contracción diaria del tronco (MXC), en comparación a la programación en función de las lecturas de tensiómetros en el suelo y de una estrategia de riego deficitario. Recientemente, Goldhamer y Fereres (2004) compararon en almendro distintos tratamientos de riego programados en función de valores umbrales de la intensidad de señal de la MXC, demostrando que era posible programar el riego en base exclusivamente a medidas de dicho indicador del estado hídrico.…”
Section: Programación Del Riegounclassified
“…In this respect, the maximum diurnal trunk shrinkage (MDS) has been proposed as a reliable water stress indicators in woody crops (see revisions by Fernández and Cuevas, 2010;and Ortuño et al, 2010). In a number of studies it has been shown that MDS in well irrigated trees depends largely on the climatic conditions (Fereres and Goldhamer, 2003;Intrigliolo and Castel, 2006b;Ortuño et al, 2006). This complicates the use of MDS in absolute terms to schedule irrigation as proposed by Bussi et al (1999).…”
Section: Introductionmentioning
confidence: 99%